The Activation of the Sox2 RR2 Pluripotency Transcriptional Reporter in Human Breast Cancer Cell Lines is Dynamic and Labels Cells with Higher Tumorigenic Potential - Iglesias, Juan Manuel; Leis, Olatz; Pérez Ruiz, Estíbaliz; Gumuzio Barrie, Juan; Garcia-Garcia, Francisco; Aduriz, Ariane; Beloqui, Izaskun; Hernandez-Garcia, Susana; Lopez-Mato, Maria Paz; Dopazo, Joaquin; Pandiella, Atanasio; Menendez, Javier A.; et al. (Frontiers in Oncology, 2014)
The striking similarity displayed at the mechanistic level between tumorigenesis and the generation of induced pluripotent stem cells and the fact that genes and pathways relevant for embryonic development are reactivated during tumor progression highlights the link between pluripotency and cancer. Based on these observations we tested whether it is possible to use a pluripotency-associated transcriptional reporter, whose activation is driven by the SRR2 enhancer from the Sox2 gene promoter (named S4+ reporter), to isolate cancer stem cells from breast cancer cell lines. The S4+ pluripotency transcriptional reporter allows the isolation of cells with enhanced tumorigenic potential and its activation was switched on and off in the cell lines studied, reflecting a plastic cellular process. Microarray analysis comparing the populations in which the reporter construct is active vs. inactive showed that positive cells expressed higher mRNA levels of cytokines (IL-8, IL-6, TNF) and genes (such as ATF3, SNAI2, KLF6) previously related with the cancer stem cell phenotype in breast cancer.